Rheological behavior of monomolecular films of bovine erythrocyte membranes: An approach towards the complexity of natural membranes - Rodriguez, Carolina Mercedes (2023)
Natural membranes, different from model membranes, are composed of a wide variety of lipids, but also proteins and glycoconjugates that make up the glycocalyx. Knowing the rheology of Langmuir (LF) films of natural membranes would allow characterizing their behavior when a disturbance is applied. The present study investigates the rheological behavior of LF constructed from natural bovine erythrocyte membranes (BEM) using two seeding methods: droplet deposition on a glass rod in contact with the interface or droplet deposition directly on the interface. . The isotherm of lateral pressure vs Area ( vs A) of LFBEM showed a single transition ( 15 mN/m) that suggests a reorganization of the components of the film, which because it is a natural membrane, contains both lipids and proteins. For the dilational rheology experiments, the FL were compressed until reaching pressures of 10 mN/m and 35 mN/m (above and below the transition), and subsequently subjected to harmonic cycles of expansion and compression with an oscillation frequency of 0.02 Hz with a 1% variation of A. The interfacial dilation modulus E* and its elastic E' (storage modulus) and viscous E'' (loss modulus) components were calculated using the phase shift (θ) between the  and A sinusoidal waves. The LF at 35 mN/m showed higher E* values, compared to the LF at 10 mN/m, regardless of the spreading method (values from the microdrop method as an example, E*10 0.521 ± 0.003 mN/m; E*35 5.35 ± 0.25 mN/m). In the same way, the compressional modulus (K) values obtained at 35 mN/m were higher than at 10mN/m. The values of E' and E'' indicate, for all the treatments, that the monolayers built from BEM present a viscoelastic behavior, with the viscous component slightly smaller than the elastic one (E’10 0.39 ± 0.1, E’’10 0.26 ± 0.1; E’35 4.43 ± 0.25, E’’35 3 ± 0.2, units in mN/m). Both the viscous and elastic behavior of this natural membrane is different from what is expected in pure lipid monolayers where the elastic component is significantly higher than the viscous one. It is postulated that compositional complexity decreases the elastic component in favor of the viscous component, that the presence of glycocalyx would contribute to the interaction with the sub-subphase and the presence of domains (observed by epiflurescence microscopy) stabilized by transient interactions, contribute to the component viscous of the film.